The nexus between food security, health outcomes, and climate change: a multisectoral approach to sustainable development in Africa - Wenxin Wang; Isaac Adjei Mensah; Samuel Atingabili; Akoto Yaw Omari-Sasu; Emmanuel Nouwati; Clement Yenube Kunkuaboor; Mu Qiao (BMC Public Health)
Abstract Background In Africa, where climatic unpredictability exacerbates food shortages and raises health risks, food security and climate change are crucial determinants influencing health outcomes. The present research investigates the significant relationship among food security, health outcomes, and climate change in African nations, and provides policy recommendations for sustainable development. Specifically, while considering the effect of climate change, the study examines how the pillars of food security proportionately affect the corresponding dimensions of health outcomes using a regional-based panel analysis. Method The study utilized a strongly-balanced panel times series data consisting of 45 counties which are sub-divided into the various regions in Africa (Northern, Eastern, Central, Western and Southern) from 2010 to 2022. Taking into account potential issues of residual cross-sectional correlations and slope heterogeneity in panel data settings, the Augmented Mean Group (AMG) estimation method is executed. The robustness of the AMG outcomes is further examined using Common Correlated Mean Group approach (CCEMG). Findings Results from the study reveals a clear relationship where food security and health outcome are positively linked in the aggregated, Central, and Western African regional panels whereas the vice versa is evidenced in Northern, Eastern and Southern Africa. Further, the respective food security pillars (food utility, accessibility, availability and utility) were evidenced to have diverse effects on health outcome dimensions (life expectancy, infant and maternal mortality, infectious disease and burden disease rates) across the regional panels in Africa, while climate change consistently worsened health outcomes and its respective dimensions among all utilized regional panels of African countries. Conclusion The study highlights the need for region-specific food security strategies in Africa, integrating robust climate adaptation measures to mitigate the negative effects of climate change on health. These insights are essential for guiding policy-makers towards sustainable solutions that address both food security and health vulnerabilities.